2017
DOI: 10.1063/1.4975341
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and charged domain walls in (K,Na)NbO3-based ferroelectric ceramics

Abstract: We report on the evidence of significant contribution of charged domain walls to low frequency dielectric permittivity in KNN ferroelectric ceramics in the frequency range 10-10 6 Hz. The effect has been attributed to the Maxwell-Wagner-Sillars relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 42 publications
1
19
0
4
Order By: Relevance
“…It was reported that the piezoelectricity was enhanced by the increasing grain size and the construction of multi-phase 14 coexistence [32,39]. As compared in Table 2, the ceramics with x=0.03 show the superior electrical properties to those of other KNN-based ceramics with an AGS of 1-2 µm [32,[40][41][42][43]. Particularly, some of the other ceramics even possess the coexisting O-T or R-T phases [32,[40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the piezoelectricity was enhanced by the increasing grain size and the construction of multi-phase 14 coexistence [32,39]. As compared in Table 2, the ceramics with x=0.03 show the superior electrical properties to those of other KNN-based ceramics with an AGS of 1-2 µm [32,[40][41][42][43]. Particularly, some of the other ceramics even possess the coexisting O-T or R-T phases [32,[40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…As compared in Table 2, the ceramics with x=0.03 show the superior electrical properties to those of other KNN-based ceramics with an AGS of 1-2 µm [32,[40][41][42][43]. Particularly, some of the other ceramics even possess the coexisting O-T or R-T phases [32,[40][41][42][43]. Therefore, the substitutions among different additives may provide more options for inducing the desired electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…22 Presently, high-resolution and scanning TEM techniques allow for observation of individual atomic displacements and, hence, give information about the internal CDW structure. With these techniques, CDWs were documented in single crystals of LiNbO 3 , 27 YMnO 3 , 28 and (Ca,Sr) 3 Ti 2 O 7 , 29,30 thin films of BiFeO 3 , 8,[31][32][33] PbTiO 3 , 34 and PZT, [35][36][37][38][39][40] and ceramics of BiFeO 3 , 41 (K,Na)NbO 3 , 42 TmMnO 3 , 43 and LuMnO 3 . 43 TEM techniques, supplemented by analyses of the energy losses of electrons (EELS) were employed recently to detect elemental components of the material in the vicinity of CDWs.…”
Section: Cdw Observationsmentioning
confidence: 99%
“…4 Sodium potassium niobate (Na, K) NbO 3 (KNN) is one of the prominent members of lead-free family, which has been studied extensively for past few decades because of its high Curie temperature, good electro-mechanical coupling effect and piezoelectric and ferroelectric properties. 5,6 With extensive research followed by a large number of scientific publications every year on KNN-based bulk ceramics, it is still very difficult to densify ceramics whose electrical properties could be reproduced, 7,8 thus hindering commercial realization. Retaining stoichiometry and high density has been the major issue related to successful fabrication of KNN ceramics, which is caused by the loss of volatile alkali species present at elevated temperatures during the fabrication process.…”
Section: Introductionmentioning
confidence: 99%